Human interaction in residential development: a conceptual framework for Malaysia / Ramli Zulkifli - Zulkifli, Ramli (Faculty of Architecture, Planning & Surveying, 1980)
For an architects and the planners they always refer to the peed to design for living. This is rather a common phrase which are too easily to expression's. But in reality how do they meet the design meant for living? However if an architect or a planner realize such an important need they must by themselves be or employed a sociologist. If the planner claim that a person's ecological surroundings are the most powerful factors influencing his happiness, but for a sociologist he will point out that it is the need for the company of others that will strongly satisfied his happiness. This research is design as such that it will involve a study of human or social interaction with a residential areas. Interactions within a residential area are accepted as an indication*of social development.